2013
DOI: 10.1177/0145721713513177
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Provider Relationships Across the Transition From Pediatric to Adult Diabetes Care

Abstract: Findings highlight the importance of enhanced provider awareness of T1D emerging adults' complex feelings about the transition in care. Improved integration of individual- and family-centered approaches to developmentally tailored diabetes care is needed to augment patient and provider relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 40 publications
0
93
1
Order By: Relevance
“…Non-adherence to treatment by patients with chronic diseases has been widely reported in the literature (23)(24)(25)(26)(27). In this study there was a considerably high rate of abandonment, more than half of the patients (61.26%) did not return for reassessment …”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Non-adherence to treatment by patients with chronic diseases has been widely reported in the literature (23)(24)(25)(26)(27). In this study there was a considerably high rate of abandonment, more than half of the patients (61.26%) did not return for reassessment …”
Section: Resultsmentioning
confidence: 57%
“…In addition, other studies point to issues related to the nature of chronic diseases such as the absence of symptoms in the early stages, the lack of severity and chronicity and an unsatisfactory doctor-patient relationship and inadequate multidisciplinary approach (23,25,27,31). Still, Massing and Portela (2015), in a descriptive exploratory study in 3978 hypertensive patients found that the evaluated did not associate the pressure control diet, but only the use of the drug (32).…”
Section: (1607%) Reason 4 -Individual and Behavioral Characteristicsmentioning
confidence: 99%
“…Some of the concepts that emerging adults with T1DM consider to be potentially beneficial include; early preparation for the transfer event [34]; provision of transition specific information to encourage active participation in the decision making process [16, 35,36]; continuity of provider during the process [37]; the opportunity to meet the adult provider during the paediatric period [34,38]; and an organised transition process [16, 35,39]. There is also an expectation that the adult clinics should be at accessible times which extend beyond the normal working day [37], are flexible in nature [39,40] and have short waiting times [16,36].…”
Section: What Do Young People Want From Their Transition Experience?mentioning
confidence: 99%
“…This may be a result of both care providers' and parents' lack of confidence in young people's ability to act independently [78,79]. However, young people have expressed a preference to see their physician alone and dissatisfaction regarding opportunities to make their own decisions [79,80]. Nonetheless, many young people desire the ongoing support of a parent, especially in the phase immediately following their transfer [80,81].…”
Section: Parent Levelmentioning
confidence: 99%
“…However, young people have expressed a preference to see their physician alone and dissatisfaction regarding opportunities to make their own decisions [79,80]. Nonetheless, many young people desire the ongoing support of a parent, especially in the phase immediately following their transfer [80,81]. It is important for adult care providers to acknowledge that some young people may still require a great deal of parental help and involvement, particularly when there is cognitive impairment and/or delayed development.…”
Section: Parent Levelmentioning
confidence: 99%